HUBUNGAN SELF CONGRUITY DENGAN WORK ENGAGEMENT PADA KARYAWAN PT. X - Nursantriani M., Zeniar Qodarin (2016)
Penelitian ini bertujuan untuk melihat hubungan antara self congruity dan work engagement yang dilakukan pada sebuah perusahaan multinasional, dengan 225 orang responden. Metode penelitian yang digunakan adalah pendekatan kuantitatif korelasional, data diambil menggunakan skala yang diadaptasi dari skala self congruity yang dibuat Sirgy et al, (1997) dan skala work engagement Megani (2012). Teknik analisis yang digunakan adalah korelasi product moment pearson.Penelitian ini menemukan bahwa terdapat hubungan antara self congruity dan work engagement di tingkat sedang, semakin tinggi self congruity semakin tinggi work engagement. Perbedaan usia dapat memengaruhi self congruity dan work engagement, sehingga organisasi idealnya mempertimbangkan perbedaan usia dalam memperlakukan karyawan. Kata kunci: work engagement, self congruity. The aim of this research was to examine the correlation between self congruity and work engagement on a multinational company. The approach on this research is correlation quantitative method. Data measured by likert scale adopted from self congruity scale established by Sirgy et al., (1997) and work engagement scale adopted by Megani from UWES (Utrecht Work Engagement Scale) established by Schaufeli & Bakker (2003). 225 respondents from various gender, age, education levels, employment status and tenure were involved on this research. Data was analyzed by product moment pearson method and one way anova to find out correlation between demographic variables. This study find out that self congruity and work engagement was related at moderate level. Respondents who have higher self congruity reported have higher work engagement. Organization need to focus on internal branding since employees lack of actual self congruity. From demographic variables, age was predisposing both self congruity and work engagement, organization should be consider on age differences. Keywords: work engagement, self congruity.